Normative Power ASEAN? Globalisation of Asian Values and Its Limits - K. Efremova (Международная аналитика, 2021)
The idea of normative power Europe, pioneered by Ian J. Manners, is usually applied to the European Union’s foreign policy. It states that the EU promotes one’s norms and values among adjacent states, determining what is “normal” in international relations. This paper, along with the burgeoning literature that looks for normative power beyond Europe, argues that the Association of Southeast Asian Nations (ASEAN) is another regional grouping that attempts to disseminate its norms and values worldwide, thus transforming itself into a nascent “normative power.” Structure-wise, this paper proceeds as follows. First, I will brieﬂy overview the concept of Ian Manner’s normative power and its applicability to Europe and Asia. Second, I will determine the Asian values that may be the basis for ASEAN’s normative stance in the world. My comparison of ASEAN and the EU’s values are structured along with several topical issues: the role of a state in people’s quotidian life and the question of human rights promotion. I exemplify the latter with the Myanmar crisis that evoked harsh criticism of the international community. I conclude that the transformation of ASEAN into a “normative power” is rather dubious since there are limits in promoting the Asian norms and values. In ASEAN, there is a group of developing countries that reject Western universalism and struggle to ﬁnd their own way in world politics.